Developing connection in community of practice: positive youth development through mentoring among youth leaders in Malaysia - Arshad, Mohd Mursyid; Ismail, Ismi Arif; Suandi, Turiman; Omar, Zoharah; Krauss, Steven Eric (Human Resource Management Academic Research Society, 2018)
Youth leadership development is a primary focus in Malaysia’s development agenda as outlined in the ‘Transformasi Nasional 2050’ or TN 50 policy initiative. Research and practice concur that the involvement of young leaders can be strengthened through wider exposure to professional training and mentoring. Yet, mentoring offers a unique learning process that enhances youth development and strengthening connection within communities. The current study was conducted to explore the contribution of mentoring to positive youth development and mentees’ sense of connection to the community and youth stakeholders. The study was conducted using a qualitative approach informed by the case study paradigm. In this study, connection resulted from the mentoring process through communication with mentors, new social and work-related networks as well as within one’s existing networks. In conclusion, data indicated that mentoring clearly has the potential to constitute the process of connection building among youth, and this process contributes to the development of their leadership capacities.